Design of high-temperature shift using waste-derived synthesis gas: Thermodynamic approach and practical reaction optimization - Gong, Ji Hyeon; Jeon, Kyung Won; Kim, Min Ju; Back, Seungki; Shim, Jae Oh; Roh, Hyun Seog; Jang, Won Jun (Energy Conversion and Management, 2023)
Herein, we verify pre-reduction conditions and H2O/CO ratio to increase activity in the HTS using Fe-Cr catalyst. It was determined that the optimal H2O/CO ratio was 2.5 through the result of calculated thermodynamic equilibrium analysis and performed HTS reaction. In the Fe-Cr catalyst, HTS reaction was performed at 350 ∼ 550 °C to find the condition that Fe2O3 convert Fe3O4 without over-reduction after reduced using 2% H2/N2, 5% H2/N2, and reactant gas at various temperature (400, 500, and 600 °C). The lower the pre-reduction temperature, the higher CO conversion, but the effect of the pre-reduction gas was not significant. In addition, as a result of performing a stability test that reduced using reactant gas at 400, 500, and 600 °C, all of which maintained stability without deactivation even though had a large range of CO conversion for 50 h. Thus, we identify that the appropriate H2O/CO ratio for HTS reaction using gas produced from waste gasification is judged to be 2.5. And during the reaction using Fe-Cr, the CO conversion showed high activity when pre-reduction temperature is 400 °C. In the case of the pre-reduction gas, the activity was insignificantly affecting the pre-reduction at 400 °C, thus it is considered appropriate to use reactant gas for practical use without the need to connect the pre-reduction gas separately.
Keywords: CO conversion; Cr catalysts; H2O/CO ratio; High-temperature shifts; Pre-reduction; Pre-reduction condition; Reactant gas; Reduction conditions; Reduction temperatures; Waste-derived synthesis gas; H2O/CO ratio; High temperature shift; Hydrogen production; Pre-reduction condition; Waste-derived synthesis gas